High Dietary Iron Has a Greater Impact on Brain Iron Homeostasis and Cognitive Function in Old Compared with Young C57BL/6J Male Mice. Issue 9 (30th June 2021) - Chen, Min; Xu, En; Zeng, Chong; Zhu, Wenjie; Zheng, Jiashuo; Chen, Huijun
ABSTRACT: Background: Brain iron accumulation is a feature of Alzheimer disease (AD) but whether a chronic dietary iron overload contributes to AD induction is unknown. We previously showed that young mice fed a high iron diet did not display cognitive impairment despite the AD pathological markers in hippocampus. Objectives: We aim to compare the impact of high dietary iron on brain pathologic changes and cognitive function in young and old mice. Methods: Male C57BL/6J mice at 1 mo and 13 mo of age were fed with either a control diet (66 mg Fe/kg; Young-Ctrl and Old-Ctrl) or a high iron diet (14 g Fe/kg; Young-High Fe and Old-High Fe) for 7 mo, and outcomes were evaluated at 8 mo and 20 mo of age. Iron concentrations in brain regions were measured by atomic absorption spectrophotometry. Perls's Prussian blue staining and amyloid-β (Aβ) immunostaining were performed. Protein expression in the cerebral cortex and hippocampus was determined by immunoblotting. Superoxide dismutase activity and malondialdehyde concentration were examined. Cognitive functions were tested with the Morris water maze system. Two-factor ANOVA was used to analyze most data. Results: Compared with Old-Ctrl mice, Old-High Fe mice showed significantly higher iron concentrations in cerebral cortex (60% higher), cerebellum (60% higher), and hippocampus (90% higher), paralleled by lower superoxide dismutase activity and greater malondialdehyde concentration in cerebral cortex and hippocampus and worse cognitive function. In contrast, these variables did not significantly differ between the 2 young groups. Nevertheless, ferritin, phospho-tau, and Aβ1–42 expression in hippocampus and ferritin and Aβ1–42 expression in cerebral cortex were induced by the high iron diet irrespective of the age of mice (40–200% greater). Conclusions: High dietary iron induced cognitive defects in old mice but not young mice, suggesting that elderly people should avoid consuming abnormally high concentrations of iron.